Characterization of Proton Dynamics for the Understanding of Conduction Mechanism in Proton Conductive Metal‐Organic Frameworks. Issue 11 (21st September 2020) - Kolokolov, Daniil I.; Lim, Dae‐Woon; Kitagawa, Hiroshi
Abstract: Proton conductivity has been traditionally investigated with various materials such as organic polymers, metal oxides, and other inorganic and organic compounds because of their potential application in the electrochemical devices. In particular, during the last decade, crystalline porous coordination polymers (PCPs) or metal‐organic frameworks (MOFs) have received considerable attention in recent years, as solid‐state proton conductors (SSPCs). To date, proton‐conductive MOFs have achieved high performance in proton conductivity (>10 −2  S cm −1 ) with rational design strategies. In addition, there are dedicated efforts to define the conduction pathway and mechanism using various experimental tools. In this review, we focus on the characterization of proton conductivity and molecular dynamics in hydrated MOFs, with selected examples to provide an understanding of the overall conduction mechanism. Abstract : This review aims to provide the interpretation and characterization of proton dynamics derived from the molecular motions in proton conductive metal‐organic frameworks. Overall conduction mechanisms related to conducting media are introduced.